High energy-storage performance of lead-free AgNbO3 antiferroelectric ceramics fabricated via a facile approach. Issue 10 (August 2021) - Wang, Xiucai; Cai, Weiqiang; Xiao, Ze; Yang, Guangguang; Yu, Xinmei; Chen, Jianwen; Chen, Dongchu; Zhang, Qingfeng; Chen, Min
Abstract: AgNbO3 lead free AFE ceramics are considered as one of the promising alternatives to energy storage applications. In the majority of studies concerning the preparation of AgNbO3 AFE ceramics, an oxygen atmosphere is required to achieve high performance, increasing the complexity of the fabrication process. Herein, a facile approach to preparing AgNbO3 ceramics in the ambient air was reported, in which the AgNbO3 ultrafine powder with stable perovskite structure was synthesized by hydrothermal method instead of the conventional ball milling process, leading to a lower temperature of phase formation and thus smaller grain size. The resulting ceramics sintered at 940 °C displayed high breakdown strength (216 kV/cm) and a recoverable energy density of 3.26 J/cm 3 with efficiency of 53.5 %. Also, the high thermal stability of recoverable energy density (with minimal variation of ≤20 %) and efficiency (≤ 10 %) over 30–150℃, enables AgNbO3 ceramics achieved to be a promising candidate for energy storage applications.